Pop modernism : noise and the reinvention of the everyday - Suárez, Juan Antonio (University of Illinois Press, 2007)
Showing that experimental art in the early 20th century was centrally concerned with the reinvention of everyday life, this work demonstrates how modernist writers and artists reworked pop images and sounds, old-fashioned and factory-made objects, city spaces, and the languages and styles of queers and ethnic 'others.'.